Adapting an Evidence-Based Home Visiting Intervention for Mothers With Opioid Dependence: Modified Attachment and Biobehavioral Catch-up - Labella, Madelyn H.; Eiden, Rina D.; Roben, Caroline K. P.; Dozier, Mary (Frontiers in Psychology, 2021)
Infants born to mothers who are dependent on opioids often have difficulty regulating behavior and physiology at birth. Without sensitive maternal care, these infants are at risk for ongoing problems with self-regulation. Mothers who are dependent on opioids may experience challenges related to their substance use (e.g., unsupportive and/or risky environment, impulse control and reward system problems) that increase the likelihood of insensitive parenting in the absence of effective intervention. In this paper, we describe a home-visiting intervention we have adapted to enhance sensitive, responsive caregiving tailored to the specific needs of mothers with opioid dependence. The original intervention, Attachment and Biobehavioral Catch-up (ABC), was designed for mothers of infants aged 6-24 months who were exposed to early adversity. ABC has been shown to enhance sensitive parenting as well as children’s behavioral and biological functioning, with positive outcomes extending into at least middle childhood. Mothers who are opioid dependent need earlier support than provided by ABC because opioid-exposed infants are often vulnerable at birth. The adapted intervention (modified ABC or mABC) includes one prenatal session and one early postnatal session, followed by 10 sessions every 2-3 weeks. In the initial two sessions in particular, mothers are helped to anticipate the challenges of caring for a baby who may be difficult to soothe while nonetheless providing sensitive care. mABC is intended to help mothers see the importance of responding sensitively so as to help infants overcome the developmental risks associated with opioid exposure. Additionally, mABC is structured to support mothers with the challenges of early parenting, especially if the mother herself was not parented sensitively. Throughout, the focus is on helping the mother nurture the distressed infant, attend to the infant’s signals, and avoid behaving in overstimulating or intrusive ways. Case examples are presented that highlight both the challenges of working with this population as well as the gains made by mothers.